1993
DOI: 10.1111/j.1432-1033.1993.tb17947.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of calmodulin with a putative calmodulin‐binding domain of inositol 1,4,5‐triphosphate 3‐kinase.

Abstract: Recombinant rat brain inositol 1,4,5‐triphosphate [Ins(1,4,5)P3] 3‐kinase was expressed in Escherichia coli as a β‐galactosidase fusion product. It could be adsorbed onto calmodulin‐Sepharose and eluted in Ca2+‐free medium as a 48‐kDa protein. Purification could be achieved in a single step. Molecular evidence for a calmodulin‐binding domain on Ins(1,4,5)P3 3‐kinase can be shown by the following approaches. (a) Inhibition of Ca2+/calmodulin stimulation by a synthetic peptide based on a candidate calmodulin‐bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…5C), as previously demonstrated for IP3KA (46). It is interesting to note in passing that the expressed IP 3 KB in particular shows evidence of being proteolyzed, much more so than the other isoforms, consistent with it being particularly sensitive to proteolysis in vitro (44) and in vivo (25); we have shown that its subcellular localization is altered by that proteolysis (25).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…5C), as previously demonstrated for IP3KA (46). It is interesting to note in passing that the expressed IP 3 KB in particular shows evidence of being proteolyzed, much more so than the other isoforms, consistent with it being particularly sensitive to proteolysis in vitro (44) and in vivo (25); we have shown that its subcellular localization is altered by that proteolysis (25).…”
Section: Resultssupporting
confidence: 85%
“…5A), highlighting in particular the essential tryptophan residue (arrow) that is highly conserved and crucial to CaM binding (46). The C. elegans enzyme is known not to bind CaM (18), and this is consistent with the absence of this tryptophan in the C. elegans sequence.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, inositol 1,4,5-trisphosphate is a major trigger of Ca 2ϩ release in the cell though binding to the inositol 1,4,5-trisphosphate receptor, which in turn is regulated by calmodulin (49). Calmodulin also binds to and regulates phosphatidylinositol 3-kinase and inositol-1,4,5-trisphosphate 3-kinase (50). Additional links are provided by calbindin D28k, which activates myo-inositol-1(or 4)-monophosphatase (51), and frequenin (neuronal calcium sensor-1), which modulates the activity of phosphatidylinositol 4-kinase (52).…”
Section: Discussionmentioning
confidence: 99%
“…CaM recognizes sequences which contain amphiphilic α-helices with clusters of positively charged and hydrophobic amino acids [38]. Sequence from Ser-156 to Leu-189 together with site Trp-165 in rat IP 3 3K-A is required for CaM binding and the enzyme activation [38,48,49]. The level of stimulation appears to be cell-, tissue-and isoform-specific [27,50] (Tab.…”
Section: +mentioning
confidence: 99%